Edukasi Mengenal Pembuatan Jahe Instan Sebagai Minuman Penghangat Tubuh - Lia Fikayuniar (Easta Journal of Innovative Community Services, 2023)
This community service goal is one of the tasks of the Tri Dharma of Higher Education, to increase the knowledge of the general public, students, and SMK students with online socialization methods about "Getting to Know the Making of Instant Ginger as a Body Warmer Drink" as a creative innovation in processed food or traditional medicine. The results of community service, namely the output targets that have been achieved are published on the faculty's youtube social media, the achievement of the obligations of tri dharma activities is fulfilled, journal publications, and increased knowledge, participants' understanding in the use of natural materials can be in the form of ideas that can be of commercial value and most importantly the community can conduct independent education. Community service concludes that after the implementation of this community service, information on the innovation of processed ginger into instant powder drinks to warm the body can be understood by participants that it has a heating effect from the content of its secondary metabolites, when the body is not good because of nausea, due to cold air and unfriendly weather.